Who is sexually faithful? Own and partner personality traits as predictors of infidelity. (May 2018) - Altgelt, Emma E.; Reyes, Melanie A.; French, Juliana E.; Meltzer, Andrea L.; McNulty, James K.
Infidelity can have harmful consequences for all those involved. Although prior research has demonstrated some reliable associations between certain personality traits and infidelity, the associations between other personality traits and infidelity are less clear. Moreover, prior research has been limited in addressing the role of partner personality and whether any effects are independent of relationship satisfaction. Thus, we pooled data from two 3-year longitudinal studies of newlywed couples to examine the associations between both couple members' personality (Big Five and narcissism) and infidelity, controlling and not controlling for marital satisfaction. Wives high (versus low) in extraversion and husbands and wives with partners high (versus low) in neuroticism or extraversion were more likely to engage in infidelity regardless of whether we controlled for satisfaction. Husbands with partners high (versus low) in narcissism were more likely to engage in infidelity, though this effect was no longer significant when controlling for satisfaction. These findings demonstrate that even predicting a behavior as self-oriented as infidelity requires considering the qualities of both couple members, highlighting the importance of adopting a dyadic approach to relationships.